Characterization of the rhipicephalus (Boophilus) microplus sialotranscriptome profile in response to theileria equi infection - Paulino, Patrícia (2022)
Funding Information: Funding: The authors disclose receipt of the following financial support for the research, authorship, or publication of this paper. The National Council for Scientific and Technological Development and the ’Carlos Chagas Filho’ Foundation for Research Support of the State of Rio de Janeiro provided financial support for this study. Publisher Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland.